Medicinal plants on the territory of the Municipality of Dospat - Dimitrova-Dyulgerova, Ivanka; Mollova, Sevdalina; Mladenova, Tsvetelina; Todorov, Krasimir Tihomirov; Stoyanov, Plamen (Journal of BioScience and Biotechnology, 2017)
The study presents data on the species diversity of medicinal plants on the territory of the Municipality of Dospat (Western Rhodopes). 332 species were described, grouped in 75 families. The Asteraceae, Lamiaceae and Rosaceae families were represented by the largest species diversity, perennial herbaceous plants being predominant. There were 72 medicinal plant species of conservation significance, including endemic, rare and protectedspecies.